Four-Week Supplementation of Water-Soluble Tomato Extract Attenuates Platelet Function in Chinese Healthy Middle-Aged and Older Individuals: A Randomized, Double-Blinded, and Crossover Clinical Trial - Tian, Zezhong; Fan, Die; Li, Kongyao; Zhao, Dan; Liang, Ying; Ji, Qiuhua; Gao, Xiaoli; Ma, Xilin; Zhao, Yimin; Mao, Yuheng; Meng, Huicui; Yang, Yan (Frontiers in Nutrition, 2022)
Background & Aims: Platelets are linked to atherosclerotic development and pathological thrombosis. Single dose of water-soluble tomato extract (WTE) which is a natural extraction can exert anti-platelet effects after 3h or 7h in British healthy people. However, the effects of WTE supplementation on platelet function in Chinese healthy middle-aged and older individuals have not been studied, and the effects or safety of 4-week WTE supplementation also remain unclear. The present study aims to determine the effects of WTE on platelet function, and explore the safety of 4-week WTE supplementation in Chinese healthy middle-aged and older individuals. Methods: A randomized, double-blinded, crossover clinical trial was conducted. Firstly, one hundred and five individuals were randomly divided into two groups that received WTE (150 mg/day) or placebo for 4 weeks. Then, after a washout period of 2 weeks, two groups exchanged groups and continued for another 4-week intervention. Platelet aggregation, P-selectin, activated GPⅡbⅢa, plasma platelet factor 4 (PF4), β-thromboglobulin (β-TG) and thromboxane B2 (TXB2) were tested at baseline, 4 weeks, 6 weeks and 10 weeks. Results: Compared with the placebo group, 150 mg/day WTE supplement for 4 weeks significantly reduced ADP-induced or collagen-induced platelet aggregation (-10.8 ± 1.8% or -3.9 ± 1.5%, P < 0.05), ADP-induced or collagen-induced platelet P-selectin expression (-6.9 ± 1.5% or -6.6 ± 1.3%, P < 0.05), ADP-induced or collagen-induced activated GPⅡbⅢa (-6.2 ± 2.0% or -3.8 ± 2.0%, P < 0.05). Besides, 4-week intervention of 150 mg WTE per day also resulted in significant reductions in plasma PF4 (-120.6 ± 33.2ng/mL, P < 0.05) and β-TG (-129.7 ± 27.5 ng/mL, P < 0.05) and TXB2 (-42.0 ± 4.0 ng/mL, P < 0.05), while had no effects on coagulation function and liver or renal function. Interestingly, 2-week washout period is enough to reverse the inhibitory effect of 4-week WTE supplement on platelet function. Conclusions: WTE supplementation for 4 weeks could moderately reduce platelet activation, aggregation and granule secretion in Chinese healthy middle-aged and older individuals, and these effects are safe. After two weeks, the inhibitory effect of 4-week WTE on platelet function can be eliminated.